2002
DOI: 10.1111/1468-2273.00225
|View full text |Cite
|
Sign up to set email alerts
|

Women in Science, Engineering and Technology: A Review of The Issues

Abstract: Concern continues to be expressed over women's difficulties in advancing their careers as academic scientists. Though some sciences may be numerically 'feminised', few women reach the upper echelons of science. Scant attention has been paid to issues of the progression of women from non-traditional backgrounds, such as those from ethnic minorities, who may be particularly disadvantaged. What research there is indicates a variation between the sciences in terms of women's careers and patterns that are replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 10 publications
0
23
0
2
Order By: Relevance
“…Women continue to be under represented in science, engineering and technology professions (Kirkup et al 2010;EC 2012;Hill et al 2010, Smith 2011) and this issue has generated a considerable body of research from a range of disciplinary perspectives (Bebbington 2002;Cohoon and Aspray 2005;Ceci and Williams 2010). While the frequently used 'leaky pipeline' metaphor has been criticised for offering too simplistic a perspective (Bickenstaff 2005), it is clear that from the point at which subject choices begin to be made at school, right through to higher level degrees at university, the numbers of women studying science, technology, engineering and mathematics (STEM) subjects progressively declines.…”
Section: Introductionmentioning
confidence: 99%
“…Women continue to be under represented in science, engineering and technology professions (Kirkup et al 2010;EC 2012;Hill et al 2010, Smith 2011) and this issue has generated a considerable body of research from a range of disciplinary perspectives (Bebbington 2002;Cohoon and Aspray 2005;Ceci and Williams 2010). While the frequently used 'leaky pipeline' metaphor has been criticised for offering too simplistic a perspective (Bickenstaff 2005), it is clear that from the point at which subject choices begin to be made at school, right through to higher level degrees at university, the numbers of women studying science, technology, engineering and mathematics (STEM) subjects progressively declines.…”
Section: Introductionmentioning
confidence: 99%
“…The limited technological training of women is also linked to their cultural background and to the geographical context in which they live which prompts women to show their creativity and work skills in traditional sectors (education, health service and retailing) rather than in technical sectors. A number of studies carried out in various countries (Bebbington, 2002) have shown that, despite the increase in the number of women graduates, including those in scientific and technological disciplines, there has not been a corresponding growth in women in the world of work, especially not in high-tech companies or in academic environments. This situation is seen even in countries like Finland where ''gender equality'' action has been taken in the professional field, and where policies have been enacted to facilitate employment for women, especially in terms of services for childcare.…”
Section: The Creation Of New Knowledgementioning
confidence: 99%
“…Some authors, like Bebbington (2002), maintain that this low presence of women in scientific and technological sectors is not so much the result of a process of self-exclusion, but rather of a phenomenon of segregation brought about by men who continue to hold the power in these contexts.…”
Section: The Creation Of New Knowledgementioning
confidence: 99%
“…Traditionally, not only women are less likely to continue higher education but also disproportionately registered for biological and non-quantitative social sciences as compared to mathematics and pure sciences (Chanana, 2004;Chakraborty, 2009;Dandapat & Sengupta, 2012). The under-representation of women students in science and technology is an international policy concern as well (Bebbington, 2002).…”
Section: Introductionmentioning
confidence: 99%